(untitled) (Integral Research, 2025)
In this interview, Dr. Rooplekha Chauhan discusses her creative journey in writing Ram Viraje Rangon Mein, a reimagining of the Ramayana through the lens of Madhubani painting and color symbolism. Inspired by her passion for art and painting, Dr. Chauhan began creating Madhubani artworks based on Ram Charit Manas and Valmiki Ramayan, which were displayed at international conferences. These paintings eventually evolved into the book, which includes Hindi and English descriptions of each artwork. Dr. Chauhan reflects on her transition from a medical professional to a spiritual and artistic pursuit after retiring in 2017. Her deep connection to the Ramayana and its ideals shaped her artistic expression, with each color symbolizing specific emotions and themes such as purity, love, courage, and peace. She emphasizes the power of visual art in making the Ramayana more accessible and relatable to contemporary audiences. Throughout the interview, Dr. Chauhan shares the challenges she faced, including learning the Madhubani style and balancing traditional symbolism with modern interpretations. She hopes her work will inspire readers to reflect on the values of truth and responsibility, as embodied in the life of Lord Ram. The book is the beginning of her ongoing exploration of other spiritual and mythological themes.